Networks of Power : Political Relations in the Late Postclassic Naco Valley - Schortman, Edward M. (Mesoamerican worlds., 2011)
Networks of Power describes who was involved in these competitions and in which network drew participated; what resources were mustered within these webs; which projects were fueled by these assets; and how, and to what extent, they contributed to the achievement of political aims. --Book Jacket.